In mammalian skeletal muscle, phosphorylation of TOMM22 by protein kinase CSNK2/CK2 controls mitophagy. Issue 2 (1st February 2018) - Kravic, Bojana; Harbauer, Angelika B.; Romanello, Vanina; Simeone, Luca; Vögtle, F.-Nora; Kaiser, Tobias; Straubinger, Marion; Huraskin, Danyil; Böttcher, Martin; Cerqua, Cristina; Martin, Eva Denise; Poveda-Huertes, Daniel; et al.
ABSTRACT: In yeast, Tom22, the central component of the TOMM (translocase of outer mitochondrial membrane) receptor complex, is responsible for the recognition and translocation of synthesized mitochondrial precursor proteins, and its protein kinase CK2-dependent phosphorylation is mandatory for TOMM complex biogenesis and proper mitochondrial protein import. In mammals, the biological function of protein kinase CSNK2/CK2 remains vastly elusive and it is unknown whether CSNK2-dependent phosphorylation of TOMM protein subunits has a similar role as that in yeast. To address this issue, we used a skeletal muscle-specific Csnk2b / Ck2β -conditional knockout (cKO) mouse model. Phenotypically, these skeletal muscle Csnk2b cKO mice showed reduced muscle strength and abnormal metabolic activity of mainly oxidative muscle fibers, which point towards mitochondrial dysfunction. Enzymatically, active muscle lysates from skeletal muscle Csnk2b cKO mice phosphorylate murine TOMM22, the mammalian ortholog of yeast Tom22, to a lower extent than lysates prepared from controls. Mechanistically, CSNK2-mediated phosphorylation of TOMM22 changes its binding affinity for mitochondrial precursor proteins. However, in contrast to yeast, mitochondrial protein import seems not to be affected in vitro using mitochondria isolated from muscles of skeletal muscle Csnk2b cKO mice. PINK1, a mitochondrial health sensor that undergoes constitutive import under physiological conditions, accumulates within skeletal muscle Csnk2b cKO fibers and labels abnormal mitochondria for removal by mitophagy as demonstrated by the appearance of mitochondria-containing autophagosomes through electron microscopy. Mitophagy can be normalized by either introduction of a phosphomimetic TOMM22 mutant in cultured myotubes, or by in vivo electroporation of phosphomimetic Tomm22 into muscles of mice. Importantly, transfection of the phosphomimetic Tomm22 mutant in muscle cells with ablated Csnk2b restored their oxygen consumption rate comparable to wild-type levels. In sum, our data show that mammalian CSNK2-dependent phosphorylation of TOMM22 is a critical switch for mitophagy and reveal CSNK2-dependent physiological implications on metabolism, muscle integrity and behavior.